MARAKNYA AKSI MAHASISWA MENENTANG KENAIKAN UKT DAN UANG PENGEMBANGAN - Fatmah, Fatmah (Berajah Journal, 2024)
Education is something important in life, one of which is college. However, looking at the current real conditions regarding higher education, not many people want that. Adolescence is a period of transition between childhood and adulthood. The age limit is not clearly defined, so many experts differ in determining the age range. External factors that cause teenagers' lack of interest in continuing their education to higher education are economic limitations/expensive educational costs and social environmental factors. The expensive cost of education, especially studying in the city, which of course requires a lot of money, causes many parents not to send their children to college.